Perlindungan Konsumen dalam E-Commerce (Studi Komparasi antara Indonesia dan Jerman) - , Erni Priliawati, SH, Drs. Paripurna Sugarda, S.H., M.Hum, LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis compares consumer protection in E-commerce between Indonesia and Germany. In principle, e-commerce transaction in Indonesia is treated the same as conventional trade agreement, so that all regulation for contract in e commerce is stipulated in Indonesian Code Civil. The regulation of consumer protection is stipulated in Indonesian Consumer protection law no. 8 of 1999. Enclosure standard business term is not forbidden as long as it does not conflict with law. Furthermore the law no. 11 of 2008 about Information and Electronic Transaction regulates digital evidence that can be used by both consumer and supplier in the event of a dispute. According to Indonesian consumer protection law, settlement of consumer dispute can be conducted through Dispute Settlement Board (BPSK) or through the court. E-commerce in Germany is regulated in the German Civil Code (BGB), in which the rights and obligations of consumers on-line transaction is ruled. Some rules in BGB are an implementation of EU law that must be implemented to national law in country members of EU. Such as Directive 97/7/EC on distant selling governing the contract, has been implemented in Germany in Article 312b-312f BGB. Settlement of consumer disputes in Germany can be also solved through the courts and through mediation, where the disputing parties make an agreement and the outcome of the mediation will be conducted by them and binding as well as court decisions. Enforcement and dispute resolution in consumer protection is regulated in Verbarucherschutzdurchsetzungsgesetz EG (VSchDG) which is also an implementaion of EU regulations concerning the enforcement of consumer protection set out in EC Directive. No. 2006/2004.